2010
DOI: 10.1111/j.1600-0889.2010.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel design of an enclosed CO<sub>2</sub>/H<sub>2</sub>O gas analyser for eddy covariance flux measurements

Abstract: A B S T R A C TThis study describes design and field performance of a new enclosed CO 2 /H 2 O gas analyser, LI-7200. Unlike present closed-path analysers, this new instrument is designed for operation with short intake tubes, with the intention to maximize strengths and to minimize weaknesses of both traditional open-path and closed-path approaches. The study provides description of the instrument, shows the principles of its operation, and explains advantages of a new design. Field results are provided from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 7 publications
2
57
0
Order By: Relevance
“…However, two different measurement devices were used for H 2 O-and CO 2 -flux measurements (open-path (LI7500, Li-Cor) at the natural site and closed-path (LI7200, Li-Cor) at the drained site), which may lead to a biased site comparison. Based on a study of Burba et al (2010) and Burba et al (2009), CO 2 and latent-heat fluxes measured by LI7500 and LI7200 show a very good agreement. The slope of the linear regression between latent-heat and CO 2 fluxes measured with these two devices for several months is almost one, and the coefficient of determination is better than 0.96.…”
Section: Appendix A: Uncertainty Of the Annual Sumsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, two different measurement devices were used for H 2 O-and CO 2 -flux measurements (open-path (LI7500, Li-Cor) at the natural site and closed-path (LI7200, Li-Cor) at the drained site), which may lead to a biased site comparison. Based on a study of Burba et al (2010) and Burba et al (2009), CO 2 and latent-heat fluxes measured by LI7500 and LI7200 show a very good agreement. The slope of the linear regression between latent-heat and CO 2 fluxes measured with these two devices for several months is almost one, and the coefficient of determination is better than 0.96.…”
Section: Appendix A: Uncertainty Of the Annual Sumsmentioning
confidence: 86%
“…Generally, ombrotrophic bogs are stronger carbon sinks than more nutrient-rich fens (Byrne et. al., 2004), while intensive land use (e.g., cropland) leads to stronger CO 2 emissions than extensive land use (Byrne et. al., 2004;Drösler et al, 2008).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…Enclosed-path systems, however, reduce flux attenuation compared to traditional closed-path systems due to shorter tube length (Burba et al, 2010;Novick et al, 2013). Sample screening of cospectra at our two study sites (data not shown) showed that frequency losses for water vapour and sensible heat flux were more pronounced at the wet fen (enclosed-path system) compared to the dry heath (closedpath system).…”
Section: Energy Balance Closure and System Performancementioning
confidence: 99%
“…This water vapor was then released as a pulse into a constant, turbulent flow of artificial air (17 lpm, 80% N 2 , 20% O 2 ), and was transported along a 13.6 m-long tube until it was divided into a 0.5 m-long sampling tube (7 lpm) and a bypass flow. From the sampling tube, the flow was directed into an infrared gas analyzer 22 and a flow-rate gauge, where after it was joined with the bypass flow in a flow module that recorded the flow rate of the whole setup. All tubes before the infrared analyzer had a diameter of 8 mm and were made of polytetrafluoroethylene (PTFE).…”
Section: @C @Smentioning
confidence: 99%